2014
DOI: 10.2337/db13-1660
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1—A Candidate Humoral Mediator for Glucose Control After Roux-en-Y Gastric Bypass

Abstract: The worldwide increase in obesity is associated with a higher prevalence of type 2 diabetes (T2D), and severe obesity occurs with the greatest risk (1). Bariatric surgery is currently the most effective treatment not only for weight loss but also for prevention or treatment of T2D in such patients (2). It leads to remission or improvement of T2D in the majority of morbidly obese (3,4). Roux-en-Y gastric bypass (RYGB) is one of the most frequently performed procedures. With RYGB, the stomach is reduced to a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…This assumption is based on previously published results, and the Ex-9 dosage used in this study has been shown to result in a 95% inhibition of the insulinotropic effect of pharmacological concentrations of GLP-1 (33,48). In our study, however, peak values of intact GLP-1 on the Ex-9/sitagliptin day reached even higher concentrations than reported previously, where the effectiveness of Ex-9 infusion has not been evaluated.…”
Section: E511 Incretins and Glucose Tolerance After Roux-en-y Gastriccontrasting
confidence: 54%
See 1 more Smart Citation
“…This assumption is based on previously published results, and the Ex-9 dosage used in this study has been shown to result in a 95% inhibition of the insulinotropic effect of pharmacological concentrations of GLP-1 (33,48). In our study, however, peak values of intact GLP-1 on the Ex-9/sitagliptin day reached even higher concentrations than reported previously, where the effectiveness of Ex-9 infusion has not been evaluated.…”
Section: E511 Incretins and Glucose Tolerance After Roux-en-y Gastriccontrasting
confidence: 54%
“…The peptide had Ͼ99.5% purity by high-performance liquid chromatography. The Ex-9 infusion rate of 900 pmol·kg Ϫ1 ·min Ϫ1 was chosen since this dosage has previously been reported to block the GLP-1R by 95% (33,48). Sita (Januvia; 100 mg) was purchased from MSD (Ballerup, Denmark) and was dispensed in capsules similar to placebo capsules by the Capital Region of Denmark Central Pharmacy (Herlev, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Certainly, our ex vivo data illustrate the ability of metformin to directly induce L cell secretion, but such an effect will be modified in vivo due to reduced dosage upon reaching the ileum and colon and by the potential for other factors to affect this response. Finally, a residual effect of GLP-1 may persist due to the submaximal GLP-1 receptor antagonism (~90%) at the chosen Ex9-39 dose, which could potentially underestimate the effect of metformin-induced GLP-1 secretion (64).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…The forearm used for blood sampling was wrapped in a heating pad (50°C) for arterialization of venous blood during the experiment. Continuous isovolemic infusions of either saline or Ex9-39 were then started at a rate of 10 ml/hour by the use of a pump (Terufusion Infusion Pump, TE-171, Terumo), for Ex9-39 corresponding to a rate of 450 pmol × kg body weight -1 × min -1 , since this dose has previously been shown to block the insulinotropic effect of synthetic GLP-1 by ~90% (64). After 30 minutes, at time 0 minutes, the patients ingested a 200 ml, 1,264 kJ (302 kcal) mixed liquid meal (chocolate-flavored Nutridrink, 36.8 g carbohydrates, 12.0 g protein and 11.6 g fat; Nutricia) mixed with a dispersion of 1,500 mg of acetaminophen in 100 ml of water (for evaluation of gastric emptying) and metformin 1,500 mg or placebo.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…The main actors in metabolic control and the reversion of complications could be the elevated concentrations of GIP, GLP-1 and PYY, resulting from an early contact between the L cell and raw nutrients [48][49][50] as well as the interaction between biliary salts and pancreatic juices, all which are promoted by procedures such as biliary pancreatic derivation, gastric bypass [51], duodenojejunal bypass [52] and adaptive enterectomy. Although it was considered a mixed procedure (restrictive and malabsorptive), in gastric bypass the malabsoptive component seems to contribute to only 11% of the overall decrease in energetic absorption [53], suggesting that it holds its main activity as a metabolic procedure.…”
Section: Surgery For Diabetes Controls An Alzheimer's Disease?mentioning
confidence: 99%